If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12(-2 + 5n) + 3 = 0 (-2 * -12 + 5n * -12) + 3 = 0 (24 + -60n) + 3 = 0 Reorder the terms: 24 + 3 + -60n = 0 Combine like terms: 24 + 3 = 27 27 + -60n = 0 Solving 27 + -60n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + -60n = 0 + -27 Combine like terms: 27 + -27 = 0 0 + -60n = 0 + -27 -60n = 0 + -27 Combine like terms: 0 + -27 = -27 -60n = -27 Divide each side by '-60'. n = 0.45 Simplifying n = 0.45
| -5a+9b=-ab+2-4a | | 2y+.5x=16 | | 8x-5=12-1 | | 5+3=-4 | | 80-6x=4x | | 10(-14n+10)+8=1368 | | 38-12x=35+6x | | 9y+3x=7 | | 5(3x+4)+8(2x+3)=31x+44 | | f+9(f-2)=69 | | -4x^2+10x-12=0 | | 3(10)+5y=15 | | 5x-6=3(x+1)+2x-9 | | [7-2q]=3 | | 7ab+6b=5ac+5 | | 3(-2)+5y=15 | | -7(14r+14)=-1078 | | 3x-7=90 | | 9x-3x+8(-2x+10)-15=7x-4x-3(2x+9)+57 | | x(6x-5)=2x^2+4x-2 | | 3(7)+5y=15 | | -.1x=3.7 | | m-12=3m+5 | | log*(x+0.1)=4 | | -2abc=4c-b | | 16x^2+35=-48x | | -9(6+c)=2c-10 | | 12=5x*25-3(50x-3) | | 7y+4(y-6)=5(y+1)-4 | | -14=-6x | | 5j+6=3j+15 | | 3(6)+5y=15 |